1993
DOI: 10.1002/ps.2780380405
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of 5,6‐dihydro‐4H‐1,3,4‐oxadiazines as potential octopaminergic insecticides

Abstract: A novel class of insecticides, the dihydrooxadiazines, was proposed following the use of molecular modelling techniques. These compounds represent conformationally restricted analogues of octopamine. Eight dihydrooxadiazines were synthesized and evaluated for useful insecticidal properties. Several of these compounds demonstrated activity against rice planthoppers, mite eggs, and tobacco budworm eggs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The oxazolidine and thiazolidine derivatives (6aÈd) were then readily converted into the corresponding hexythiazox analogues (1bÈg and 10a, b) by treatment with cyclohexyl isocyanate (8) or phenyl isocyanate (9) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The oxazolidine and thiazolidine derivatives (6aÈd) were then readily converted into the corresponding hexythiazox analogues (1bÈg and 10a, b) by treatment with cyclohexyl isocyanate (8) or phenyl isocyanate (9) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…based on these atoms was 0.1 A. The two functionalities deemed to be essential to octopaminergic pesticidal action (14), a phenyl ring and a suitably situated amino group, appear to be conserved in 4. A similar comparison between the octopaminergic pesticide, chlordimeform 2, and octopamine 1 also resulted in identification of common structural features (26).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, dihydrooxadiazines were identified (14,15) as novel octopaminergic insecticides. They were shown to be octopamine agonists in the two-spotted spider mite, Tetranychus urticae (16), and in the American cockroach, Can For personal use only.…”
Section: Nhzmzl4--)-ohmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of the OCT 1 receptor elevates the intracellular level of Ca 2+ , while the activa-tion of the other OCT receptors leads to an increase in the intracellular level of the second messenger cAMP by activating adenylate cyclase (Evans, 1981;Harmar and Horn, 1977;Nathanson, 1979;Nathanson and Greengard, 1973). The adenylate cyclase-coupled OCT receptors have been considered to be a potential target of insectistatic or insecticidal compounds (Dekeyser et al, 1993;Kadir and Knowles, 1991;Nathanson and Hunnicutt, 1981). The research to date has found that a variety of compounds act as agonists and antagonists of OCT 2 and OCT 3 receptors (Roeder, 1999).…”
Section: Introductionmentioning
confidence: 96%